2014
DOI: 10.1123/jab.2013-0147
|View full text |Cite
|
Sign up to set email alerts
|

Functional Data Analyses for the Assessment of Joint Power Profiles During Gait of Stroke Subjects

Abstract: Lower extremity kinetic data during walking of 12 people with chronic poststroke were reanalyzed, using functional analysis of variance (FANOVA). To perform the FANOVA, the whole curve is represented by a mathematical function, which spans the whole gait cycle and avoids the need to identify isolated points, as required for traditional parametric analyses of variance (ANOVA). The power variables at the ankle, knee, and hip joints, in the sagittal plane, were compared between two conditions: With and without wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We plotted our estimates of pairwise comparison functions between pre-and post-fatigue, as well as 95 % confidence interval (CI) bands to determine significant differences. Differences were identified where the curve plus its effect size (95 % CI) did not cross the zero line [1]. We used the fda package in the statistical program "R" (version 2.15.1) for all FANOVA s.…”
Section: Discussionmentioning
confidence: 99%
“…We plotted our estimates of pairwise comparison functions between pre-and post-fatigue, as well as 95 % confidence interval (CI) bands to determine significant differences. Differences were identified where the curve plus its effect size (95 % CI) did not cross the zero line [1]. We used the fda package in the statistical program "R" (version 2.15.1) for all FANOVA s.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of an ensemble of curves and other comparisons of data over time is not a completely novel concept, but the application strength and sophistication used in the analysis varies. A recent paper describing a functional data analysis of variance approach (FANOVA) also used B-spline basis functions ( Andrade et al, 2014 ). This paper proposed the simple effects model with one factor, as in y jy ( t ) = μ ( t ) + α j ( t ) + ε jy ( t ), where μ ( t ) is the overall functional mean and is the effect of the jth level of Factor A.…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted three separate functional analyses for the sagittal plane ankle, knee and hip joint angles (R 2.15.1, R development core team, http://madison.byu.edu/FDA.html ). We used a modified version of a functional data analysis procedure ( Andrade et al, 2014 ). This requires use of basis functions, warping and a statistical framework, as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While statistical methods including t-test, ANOVA and covariance analysis were used to analyze and test the coupling or grouping across subjects based on statistic measurements for various applications of kinematic and/or physiological data (Park et al, 2017), advanced techniques of functional data analysis and machine learning demonstrated more promising results in regard to high-dimensional multi-variate gait data (Park et al, 2017). In various health related studies, supervised learning methods, such as SVM, k-nearest neighbors (KNN), linear discriminative analysis (LDA), neural network (NN), were employed for predicting or classifying in between of target and control cohorts, and usually combined with dimensionality reduction approaches, such as principle component analysis (PCA) to discover information from a high-dimensional space (Deluzio & Astephen, 2007;Coffey et al, 2011;Fukuchi et al, 2011;Eskofier et al, 2012;Andrade et al, 2013;Phinyomark et al, 2014;Janidarmian et al, 2015;Derlatka & Bogdan, 2015;Tucker et al, 2015;Watari et al, 2016;Phinyomark et al, 2016;Rida et al, 2016). In addition, some researches were focused on modeling motion dynamics of multivariate kinematic data using hidden Markov model (Mannini & Sabatini, 2012) and Bayesian network (Moon & Pavlović, 2008) for gait pattern recognition.…”
Section: Pattern Recognition and Analysis Of Human Motion Datamentioning
confidence: 99%